Reuse of ancient megalithics monuments during Metal Ages: the dolmen of Serrinha (Monforte, Portugal). - Rocha, Leonor (2019)
The set of funerary megalithic monuments in the Alentejo region (Portugal) presents a great variety in its architectures, but also in their uses and reuses. Although often undocumented (in the case of ancient excavations), the collections in the Museums prove their use between the Neolithic Age and at least the Iron Age. The Dolmen of Serrinha (Monforte) recently excavated by the signatories, is a good example of the reuse of necropolis spaces during Metal Ages.